EFL Teachers’ Perceptions of Technology-Enhanced Differentiated Reading Instruction (TEDRI): Issues and Challenges - Riswandi, Diki; Mujiyanto, Januarius; Fitriati, Sri Wuli; Sukarno (Journal of language teaching and research, 2025)
English as a Foreign Language (EFL) teachers are under pressure to address today’s educational demands, such as the use of digital technology in the classroom and the need to improve students’ literacy skills. To shed light on these matters, this study examines the EFL teachers’ perceptions of implementing Technology-Enhanced Differentiated Reading Instruction (TEDRI) in the classroom and explores how teachers are adapting to its use. Interview data were collected from six EFL teachers. The findings show that teachers perceive the implementation of TEDRI to be positive overall. However, some teachers also face difficulties in applying TEDRI, such as the need to adjust their reading instruction methods as well as a lack of experience in integrating technology in TEDRI.